STRATEGI TINDAK LANJUT HASIL SUPERVISI - Rutin Winarsih; Ahmad Manshur (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2026)
The follow-up of supervisory results is a crucial stage in improving the quality of learning and teacher performance. This study employs a library research method with a qualitative approach by analyzing various relevant journals and references. The findings indicate that supervisory follow-up, which includes planning, coaching, training, monitoring, and further evaluation, is able to enhance teacher competence and the effectiveness of the learning process. In addition, supervisory follow-up plays an important role in strengthening quality culture, improving teacher professionalism, and building collaborative relationships between principals and teachers. Although there are challenges such as limited time, resources, and teacher resistance, these obstacles can be overcome through proper management, persuasive approaches, and integrating follow-up programs into institutional planning. Thus, the follow-up of supervisory results becomes a strategic instrument in improving the quality of education, particularly in Islamic educational institutions